Brill's companion to Aineias Tacticus - Pretzler, Maria; Barley, Nick, Ph.D (Brill's companions in classical studies., 2018)
"Brill's Companion to Aineias Tacticus is a collection of articles on the significance of the earliest Greek handbook on military tactics. Aineias' (Aeneas) wrote his Poliorketika in the mid-fourth century BC, offering a unique perspective on contemporary Greek city-states, warfare and intellectual trends. We offer an introduction to Aineias and his work, and then discuss the work's historical and intellectual context, his qualities as a writer, and aspects of his work as a historical source for the Greek polis of the fourth century BC. Several chapters discuss Aineias' approach to warfare, specifically light infantry, mercenaries, naval operations, fortifications and technology. Finally, we include a lengthy study of the reception of ancient military treatises, specifically Aineias' Poliorketika, in the Byzantine period. Contributors are: Nick Barley, Marco Bettalli, Ben Gourley, Robin Lane Fox, Peter Liddel, Maria Pretzler, Philip Rance, Tracey Rihll, Jim Roy, Graham Shipley, Philip de Souza, José Vela Tejada, and David Whitehead."--Provided by publisher.